2021
DOI: 10.1007/s40314-021-01505-7
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid radial basis function methods of lines for the numerical solution of viscous Burgers’ equation

Abstract: An efficient and accurate hybrid radial basis function (HRBF) method is proposed to numerically solve the quasi-linear viscous Burgers' equation. Two different RBFs are combined: an infinite smooth RBF defined by a shape parameter and a piecewise smooth RBF independent of the shape parameter. This combination formulates a family of HRBF methods, which is then used to approximate the spatial operator of the viscous Burgers equation. An efficient high-order solver is then used to integrate in time the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
(176 reference statements)
0
7
0
Order By: Relevance
“…As presented in [24], by coupling the infinite smoothing RBFs (φ 1 ), such as MQ, IMQ, and GA, with the piecewise smooth RBFs Sn and TPS RBFs (φ 2 ), the HRBF is constructed and can be defined as…”
Section: The Construction Of Hrbfsmentioning
confidence: 99%
See 4 more Smart Citations
“…As presented in [24], by coupling the infinite smoothing RBFs (φ 1 ), such as MQ, IMQ, and GA, with the piecewise smooth RBFs Sn and TPS RBFs (φ 2 ), the HRBF is constructed and can be defined as…”
Section: The Construction Of Hrbfsmentioning
confidence: 99%
“…It has been dictated in Mishra's article [33] that a small value of the weight parameter w usually gives acceptable accuracy with a stable spectrum (when all the eigenvalues of the differentiation matrix lie in the left half-plane). In Manzoor's article [24], the authors calculated many numerical examples and concluded that in most of the test examples, for the three types of hybrid radial basis functions, MQ + S3, GS + S3, and IMQ + S3, the weight parameter w = 10 −3 works best. On the other hand, for the three types of hybrid radial basis functions, MQ + TPS, GS + TPS, and IMQ + TPS, the weight parameter w = 10 −9 .…”
Section: The Construction Of Hrbfsmentioning
confidence: 99%
See 3 more Smart Citations